The Online Mini Thesis Supervision: Students’ Perception - Intan satriani; Setya Resmini; Ula Nisa El Fauziah (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2023)
In the current COVID-19 era, teaching and learning process is mostly conducted through online. On the point of that, this situation effects the practice of mini thesis writing supervision. Based on the research background, this research is aimed at finding out students’ perception of the implementation of online mini thesis writing supervision. The questionnaire format used in this research is adopted from Kintama, Larasati, and Yuliana (2021). Limitation of this research was on choosing five criteria. The criteria were students’ readiness, types of supervising session, students’ understanding, internet facilities readiness, application used during online supervising session, and duration of students’ mini thesis revision. The questionnaire was distributed to 32 students of English Education program who deal with mini thesis supervising session. The data were collected by distributing questionnaire to the participants using google form. Descriptive qualitative was used to analyze and present the data. The results showed that the students get positive responses towards the implementation of online supervising session.